Developing Enterprise-wide Business Process Management Capability: A Teaching Case from the Financial Sector. Issue 2 (November 2018) - Bandara, Wasana; Abbott, Charon; Mathiesen, Paul; Meyers, Lara; Nagra, Mindy
Continuously managing business processes is globally a high organisational priority. The necessity for organisation-wide process management approaches (as opposed to ad hoc initiatives) is widely recognised. Yet, the required skills and capabilities for such enterprise-wide BPM is a well-known gap, with little resources to date to address this. This teaching case is based on the Bank of Queensland (BOQ—one of the oldest financial institutions in Australia). The narrative provides an overview of a range of Enterprise level business process management (hereafter referred to as 'E-BPM') activities that have taken place to date at BOQ to build its E-BPM capability. The teaching case presents how the development of E-BPM capability is a continuous journey which requires applied management and strong governance, and articulates some of the issues encountered when embedding BPM within an organisational structure. Based on the case, a series of student activities pertaining to E-BPM practices covering key aspects of BPM governance, strategic alignment, culture, people, IT, methods, etc., is provided (with model answers). This case is complemented by a rich set of teaching notes, making it a valuable resource that can be easily and directly applied for E-BPM training.